2011
DOI: 10.1021/nn201227b
|View full text |Cite
|
Sign up to set email alerts
|

Universal Scaling of the Figure of Merit of Plasmonic Sensors

Abstract: We demonstrate an improvement by more than 1 order of magnitude of the figure of merit (FoM) of plasmonic nanoparticle sensors by means of the diffractive coupling of localized surface plasmon resonances. The coupling in arrays of nanoparticles leads to Fano resonances with narrow line widths known as surface lattice resonances, which are very suitable for the sensitive detection of small changes in the refractive index of the surroundings. We focus on the sensitivity to the bulk refractive index and find that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
261
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(267 citation statements)
references
References 32 publications
5
261
1
Order By: Relevance
“…The increased LDOS and enhanced outcoupling are responsible for this increased emission. It is worth pointing out that having both surface lattice resonances and quasi-guided modes are beneficial for light management techniques not only in the fields of solid state lighting but also for thin films solar cells [46] and sensors [47].…”
Section: Discussionmentioning
confidence: 99%
“…The increased LDOS and enhanced outcoupling are responsible for this increased emission. It is worth pointing out that having both surface lattice resonances and quasi-guided modes are beneficial for light management techniques not only in the fields of solid state lighting but also for thin films solar cells [46] and sensors [47].…”
Section: Discussionmentioning
confidence: 99%
“…Schatz et al [11,12] have first suggested that these narrow resonances are possible in regular arrays of NPs, while Markel has elaborated the theory [13]. Several experimental verifications have also been provided [14][15][16][17][18][19][20][21][22][23], and considering the very narrow linewidth achievable (few nanometers), results hold promises for many applications in lasing, sensing, and metamaterials [24]. An interesting possibility is to study the coupling between diffractive and plasmon modes in the condition λ RA < λ LSP .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with LSPRs, SLRs possess much higher Q's, and the associated polaritons can propagate over tens of unit cells in the plasmonic crystal [12]. The relevance of SLRs for enhanced, directional, and polarized light emission [11,14] and sensing [15] has been recently demonstrated. Although the coupling of surface modes in periodic metallic structures has attracted much interest [16][17][18][19], especially for its connection with frequency stop gaps [20], coupled SLRs have not yet been discussed.…”
mentioning
confidence: 99%
“…We have also calculated the variable-angle extinction spectra of the array in Fig. 1(b) with the coupled dipole model [5][6][7]15], which treats each particle as a radiating dipole and calculates the dipolar interactions of all particles in the array. The results obtained were in significant disagreement with the measurements and the simulations, and we therefore do not show the spectra here.…”
mentioning
confidence: 99%